2019
DOI: 10.3390/bs9020020
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Profile of People with High-Functioning Autism Spectrum Disorders

Abstract: Several studies have examined the cognitive profile of people with high-functioning autism spectrum disorders (ASD) (IQ > 70), and its relationship with the symptoms of ASD and attention deficit hyperactivity disorder (ADHD), using the Wechsler Intelligence Scale for Children-IV (WISC-IV). However, no data exist on the similarities or differences in this profile in less affluent countries. The present study examined the cognitive profile and its relationship with the symptoms of ASD and ADHD in 30 subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
3
8
0
1
Order By: Relevance
“…Analyzing more in detail the single sub-indices of the intelligence, we found that Verbal comprehension skills (VCI) were significantly higher in ASD-HF group than all other groups. In Rabiee’s study [ 3 ], ASD-HFs subjects showed good Verbal skills (VCI) and Processing Speed abilities (PSI), as well as the control group; in our study, on the other hand, the ASD-HF group scored higher than the TD group in the verbal skills (VCI), but lower in the Processing Speed abilities (PSI), consistent with the results of the study by Oliveras Rentas [ 10 ]. As for Visual Perceptual Reasoning (PRI) skills, the ASD-HF group performed significantly better than the other three groups.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Analyzing more in detail the single sub-indices of the intelligence, we found that Verbal comprehension skills (VCI) were significantly higher in ASD-HF group than all other groups. In Rabiee’s study [ 3 ], ASD-HFs subjects showed good Verbal skills (VCI) and Processing Speed abilities (PSI), as well as the control group; in our study, on the other hand, the ASD-HF group scored higher than the TD group in the verbal skills (VCI), but lower in the Processing Speed abilities (PSI), consistent with the results of the study by Oliveras Rentas [ 10 ]. As for Visual Perceptual Reasoning (PRI) skills, the ASD-HF group performed significantly better than the other three groups.…”
Section: Discussionsupporting
confidence: 91%
“…From the comparative analysis of the cognitive abilities, we found that the global intelligence, represented by the Total Intelligence Quotient (TIQ), was in normal range in all three clinical groups. Furthermore, the ADHD and SLD group scored significantly lower compared to ASD-HF group and control group, without significant differences between them [ 3 ]. Analyzing more in detail the single sub-indices of the intelligence, we found that Verbal comprehension skills (VCI) were significantly higher in ASD-HF group than all other groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations